2019
DOI: 10.1097/mpa.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mesenteric Mass in Patients With Midgut Neuroendocrine Tumors

Abstract: Objectives In this study, we used the institutional pathological and clinical databases from The Mount Sinai Hospital to investigate the impact of mesenteric mass on clinical and staging features in small intestinal neuroendocrine tumors. Methods Demographic, clinical, and staging data were collected. Tumor-node-metastasis stage was assigned according to the American Joint Committee on Cancer eighth edition staging manual. We used a χ2-square test to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a study of 72 cases of SBNET resections, Gonzalez et al ( 45 ) demonstrated that the presence of a mesenteric mass was significantly associated with lymph nodal and liver metastasis, lymphovascular invasion, T3 or T4 disease, and increased disease progression and death. Malik et al ( 46 ) also found that patients with a mesenteric mass were more likely to have advanced T status and confirmed that mesenteric involvement represented more extensive disease and was also associated with more aggressive treatment. If feasible, surgery was required for the primary tumor, regional LNs, and mesenteric masses.…”
Section: Discussionmentioning
confidence: 86%
“…In a study of 72 cases of SBNET resections, Gonzalez et al ( 45 ) demonstrated that the presence of a mesenteric mass was significantly associated with lymph nodal and liver metastasis, lymphovascular invasion, T3 or T4 disease, and increased disease progression and death. Malik et al ( 46 ) also found that patients with a mesenteric mass were more likely to have advanced T status and confirmed that mesenteric involvement represented more extensive disease and was also associated with more aggressive treatment. If feasible, surgery was required for the primary tumor, regional LNs, and mesenteric masses.…”
Section: Discussionmentioning
confidence: 86%
“…This could also be related to the small size of our study population. Indeed, Malik et al [22] showed an association between the presence of an MM on pathological specimen and symptoms in 302 studied patients, but the authors mixed symptoms related to carcinoid and LTR symptoms. To clarify the results in the present series and because these 2 situations require 2 different treatments (somatostatin analogs for one and quick surgery for the other), we deliberately separated carcinoid symptoms and LTR symptoms.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Most patients with SI-NETs (nearly 80%) present nonspecific symptoms mainly related to the local effect of MLNM than to the primary tumor [ 4 , 5 , 66 ]. Among them, 12.5% to 33% need emergency surgery [ 5 , 12 , 67 ].…”
Section: Surgerymentioning
confidence: 99%